2021
DOI: 10.3390/brainsci11060779
|View full text |Cite
|
Sign up to set email alerts
|

Acid Precipitation and the Prevalence of Parkinson’s Disease: An Ecologic Study in U.S. States

Abstract: Although the etiology of Parkinson’s disease (PD) is unknown, potentially informative clues lie in its geographic distribution. PD prevalence rates within the U.S. are significantly higher in the Midwest and Northeast, a pattern that resembles the geographic distribution of acid precipitation (“acid rain”). Using linear and multivariable regression, we examined state-wide data on PD prevalence in relation to environmental factors including total precipitation, the acidity of precipitation, the use of well wate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…The National Survey recognized four categories of water systems, defined by the size of the population served: LSL1, for populations < 10,000; LSL2, for populations of 10,000–50,000; LSL3 for populations > 50,000, and LSL4, for all systems combined. We included other variables in our analyses that were previously linked to PD prevalence: the Acid Precipitation Index (a measure of the acidity and quantity of acid rain), well water use by state, and state-wide releases of sulfuric acid [4] .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The National Survey recognized four categories of water systems, defined by the size of the population served: LSL1, for populations < 10,000; LSL2, for populations of 10,000–50,000; LSL3 for populations > 50,000, and LSL4, for all systems combined. We included other variables in our analyses that were previously linked to PD prevalence: the Acid Precipitation Index (a measure of the acidity and quantity of acid rain), well water use by state, and state-wide releases of sulfuric acid [4] .…”
Section: Methodsmentioning
confidence: 99%
“…Acid rain (synonyms , acid precipitation, acid deposition) is precipitation with a pH < 5.6 (neutral pH = 7). Acid rain could play an etiologic role in PD by leaching lead from watersheds and plumbing into drinking water [4] . The majority of lead in tap water is derived from lead service lines (LSLs), the underground pipes that connect homes to municipal water sources.…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers have conducted in-depth studies on climate change effects and related issues. For example, research has shown that climate change is associated with deteriorating human health (Rhea et al, 2021), the incidence of Parkinson's is positively related to acid precipitation (Schwartz and Williamson, 2021), climate change can lead to unfavourable plant growth (Zandalinas et al, 2021), global warming increases the risk of flooding (Kam et al, 2021), and any one of the other climate factors may produce a domino effect as global warming increases (Wunderling et al, 2021). Considering climate change's negative impact on the earth, researchers are continually exploring the anomalies' mechanisms and suggesting ways to mitigate them, such as identifying factors that accelerate global warming (Richardson, 2022), analysing ways to mitigate global warming through systems thinking and sustainable development (Mella, 2022), analysing ozone layer depletion causes and potential recovery methods (Akhobadze, 2020), and proposing recovery and complementary resilience plans in response to climate change (Woodruff et al, 2022).…”
Section: Introductionmentioning
confidence: 99%